2014
DOI: 10.1111/add.12563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of depressive symptoms on antecedents of lapses during a smoking cessation attempt: an ecological momentary assessment study

Abstract: Aims: To investigate pathways through which momentary negative affect and depressive symptoms affect lapse risk. Design: Ecological Momentary Assessment was carried out during two weeks after an unassisted smoking cessation attempt. A three-month follow-up measured smoking frequency. Setting: Data were collected via mobile devices in German-speaking Switzerland. Participants: A total of 242 individuals (age 20-40, 67% men) reported 7,112 observations. Measurements: Online surveys assessed baseline depressive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 85 publications
3
22
1
Order By: Relevance
“…The strong predictive values of momentary low self-efficacy and being around smokers on lapse are in line with RP theory ( Marlatt and Donovan, 2005 ) and other EMA studies ( Shiffman et al, 1996a , 1996b ; Gwaltney et al, 2001 ; Gwaltney et al, 2005a ; van Zundert et al, 2010 ; Kirchner et al, 2012 ; Brodbeck et al, 2014 ). In contrast to previous studies, the influences of negative affect, positive outcome expectations, and craving on lapse were less consistent ( Killen and Fortmann, 1997 ; Shiffman et al, 1997 ; Dijkstra and Borland, 2003 ; Shiffman and Waters, 2004 ; Gwaltney et al, 2005a ; McCarthy et al, 2006 ; Minami et al, 2014 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The strong predictive values of momentary low self-efficacy and being around smokers on lapse are in line with RP theory ( Marlatt and Donovan, 2005 ) and other EMA studies ( Shiffman et al, 1996a , 1996b ; Gwaltney et al, 2001 ; Gwaltney et al, 2005a ; van Zundert et al, 2010 ; Kirchner et al, 2012 ; Brodbeck et al, 2014 ). In contrast to previous studies, the influences of negative affect, positive outcome expectations, and craving on lapse were less consistent ( Killen and Fortmann, 1997 ; Shiffman et al, 1997 ; Dijkstra and Borland, 2003 ; Shiffman and Waters, 2004 ; Gwaltney et al, 2005a ; McCarthy et al, 2006 ; Minami et al, 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…Ecological momentary assessment studies have highlighted the importance of momentary factors on smoking lapse and relapse. Self-confidence to resist a cigarette (self-efficacy) is a key dynamic predictor of lapse and relapse ( Gwaltney et al, 2002 ; Shiffman et al, 2002 ; Gwaltney et al, 2005a , 2005b ; van Zundert et al, 2010 ; Kirchner et al, 2012 ; Brodbeck et al, 2014 ). However, 1 study ( Minami et al, 2014 ) could not confirm this.…”
mentioning
confidence: 99%
“…This decrease produced during treatment in all the groups might be due to the fact that the treatment includes psychological strategies that may also be useful for mood management (e.g., problem solving, stress management), but after completing the treatment or if there is a relapse, these positive effects on mood disappear. Ischaki and Gratziou (2009) and Brodbeck et al (2014) point to self-efficacy and self-esteem as mediating variables between depression and smoking cessation. Compared with relapsers or with those who never stopped smoking, those who remain abstinentdespite not differing in depression scores at the beginning of treatment-probably use the strategies to maintain abstinence that they learned throughout the treatment, thereby increasing their self-efficacy and the likelihood of not relapsing (Marlatt and Donovan, 2005).…”
Section: Smokers (N¼ 49)mentioning
confidence: 99%
“…People with depression also have more difficulty quitting smoking (Ziedonis et al, 2008) and are more likely to relapse (Brodbeck et al, 2014;Zvolensky et al, 2015). In their meta-analysis, Hitsman et al (2013) found that the existence of a history of major depression in the past, but not in the present, hinders the achievement of abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence of depressive symptoms is associated with undergoing a stronger withdrawal syndrome, with more difficulty to quit smoking, and with a greater likelihood of relapse (Brodbeck, Bachmann, Brown, & Znoj, 2014), the positive results obtained in O.L. 's smoking cessation intervention confirm that achieving abstinence from tobacco is, in many cases, associated with a reduction of stress and depressive and anxious symptomatology, as well as with an improvement in mood and the perception of quality of life (Taylor et al, 2014).…”
Section: Resultsmentioning
confidence: 90%